Intervensi Mindfulness sebagai Upaya Pengelolaan Kecemasan Remaja di Lingkungan Sekolah Kejuruan - Rahmawati, Arni Nur; Haniyah, Siti; Suryani, Roro Lintang; Fitriana, Adita Silvia (Journal of Health Innovation and Community Services, 2025)
Abstract: Academic anxiety is a common psychological problem experienced by adolescents, particularly vocational high school (SMK) students, impacting their academic performance and mental well-being. This community service program aims to reduce student anxiety levels through education and training in mindfulness breathing techniques using the STOP (Stop, Take a Breath, Observe, Proceed) approach. The activity was conducted at SMK Mulia Husada, Banyumas Regency, involving 11th-grade students, and was carried out in a single training session that included counseling, interactive discussions, and hands-on practice. Initial screening results indicated that most students were in the moderate anxiety category. After the training, more than 90% of students reported feeling calmer and stated that the techniques taught were easy to apply in their daily lives. This program demonstrated that mindfulness training, packaged in an educational and participatory manner, is effective as a promotive and preventive intervention in efforts to strengthen adolescent mental health in the school environment. This activity can be replicated and developed as part of a guidance and counseling program or routine school-based activities to support student psychological resilience.